The Effects of Task Complexity, Professional Auditor Skepticism, and Motivation of Auditors Against Quality of Audit on Public Accountants in Bali - I K Haryana; I B A Yasa; K Nurhayanti (Journal of Applied Sciences in Accounting, Finance, and Tax, 2019)
Audit quality is the probability of an auditor in finding violations and reporting an error or misappropriation that Occurs in the client's accounting system. Quality is influenced by various factors, while the factors used in this study to PROVE the effect on audit quality include the complexity of tasks, Skepticism of professional auditors, and auditors motivation. The purpose of this study is to Determine the effect of task complexity, Skepticism of professional auditors and auditors on audit quality motivation at KAP in Bali. Population in this research is all Public Accounting Firm Bali exist in the which have been registered in the directory of Certified 2017. Sampling method in this research use or saturated sample census method. The number of respondents used was 71 respondents. The hypothesis was tested with a significance level of 5% (percent) using Partial Least Square (PLS) through the SmartPLS 3.0 application. The results Showed that the complexity of tasks, professional Skepticism of auditors and auditors motivation have a significant effect on audit quality.